1997
DOI: 10.1063/1.475306
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative chemisorption of methane on Ir(111): Evidence for direct and trapping-mediated mechanisms

Abstract: Molecular beam and bulb gas techniques were employed to study dissociative chemisorption of methane on Ir(111). The initial dissociative chemisorption probability (S0) was measured as a function of incident kinetic energy (Ei), surface temperature, and angle of incidence (θi). As the incident kinetic energy increases, the value of S0 first decreases and then increases with Ei indicating that a trapping-mediated chemisorption mechanism dominates methane dissociation at low kinetic energy, and a direct mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 50 publications
11
135
1
Order By: Relevance
“…The E b values obtained for the Ir(111) terraces are consistent with the apparent activation energy obtained experimentally for the high energy part of the sticking curve 13,14 . Nevertheless, the lowest E b value found is considerably higher than the apparent activation energy extracted from experiments corresponding to low-energy molecules impinging Ir(111).…”
Section: Transition States For Ch3· · ·H Dissociationsupporting
confidence: 74%
See 2 more Smart Citations
“…The E b values obtained for the Ir(111) terraces are consistent with the apparent activation energy obtained experimentally for the high energy part of the sticking curve 13,14 . Nevertheless, the lowest E b value found is considerably higher than the apparent activation energy extracted from experiments corresponding to low-energy molecules impinging Ir(111).…”
Section: Transition States For Ch3· · ·H Dissociationsupporting
confidence: 74%
“…In such a case, trapping acts as a precursor for dissociation 15 . For CH 4 /Ir(111), two experimental groups independently obtained very similar sticking curves S 0 (E i ) pointing to precursor mediated dissociative adsorption at low impact energies 13,14 . Combining molecular beam and bulb experiments, Seets et al determined an apparent activation energy of 0.28 eV for the low kinetic energy regime E i 0.15 eV 13 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…2, the rate constant for PMD follows a Brønsted-Evans-Polanyi relation with the total adsorption energy of a CH 3 fragment and an H atom as catalyst descriptors. At high kinetic energies (high temperatures) the precursor mediated dissociation shifts gradually to a direct dissociation (DD) mechanism as indicated by molecular beam and thermal bulb experiments of Seets et al [26,27]. Strong evidence exists that the reaction is structure sensitive [28].…”
Section: Dry Reformingmentioning
confidence: 98%
“…1.͒ Molecular beam experiments in which the dissociation probability was measured as a function of translational energy have observed that the dissociation probability is enhanced by the normal incidence component of the incidence translational energy. [2][3][4][5][6][7][8][9][10][11][12] This suggests that the reaction occurs primarily through a direct dissociation mechanism at least for high translational kinetic energies. Some experiments have also observed that vibrationally hot CH 4 dissociates more readily than cold CH 4 , with the energy in the internal vibrations being about as effective as the translational energy in inducing dissociation.…”
Section: Introductionmentioning
confidence: 99%